Protective Role of microRNA-31 in Acetaminophen-Induced Liver Injury: A Negative Regulator of c-Jun N-Terminal Kinase (JNK) Signaling PathwaySummary - Jianxin Zheng (Elsevier, 2021)
Background & Aims: Sustained c-Jun N-terminal kinase (JNK) activation plays a major role in drug-induced liver injury (DILI). Stress-responsive microRNA-31 (miR-31) has been implicated in regulating different cellular damage, and JNK activation could induce miR-31 expression. However, the regulatory role of miR-31 in DILI has not been studied previously. We aimed to investigate whether miR-31 could ameliorate DILI and ascertain potential molecular mechanism. Methods: miR-31 gene knockout (31-KO) and wild-type C57BL/6J mice were used to construct an acetaminophen (APAP)-induced DILI model. Primary mouse hepatocytes, as well as alpha mouse liver 12 (AML-12) cell lines, were used for in vitro experiments. Argonaute 2–associated RNA immunoprecipitation combined with high-throughput sequencing were performed to identify specific targets of miR-31. Results: 31-KO mice showed a higher mortality rate, liver transaminase levels, and hepatic necrosis compared with those in wild-type mice after APAP-induced hepatotoxicity. The protective role of miR-31 on hepatocytes has been analyzed via constructing bone marrow chimeric mice. Mechanistically, we found that hepatic JNK phosphorylation increased significantly in 31-KO mice. This caused mitochondrial phosphorylated Src (p-Src) inactivation and more reactive oxygen species production, which directly amplifies hepatocyte necrotic cell death, while administration of JNK-specific inhibitor SP600125 could abrogate the differences. Moreover, bioinformatics analysis of RNA immunoprecipitation combined with high-throughput sequencing identified that guanosine triphosphatase, cell division cycle protein 42 (Cdc42), the upstream molecule of JNK signaling, was the specific target of miR-31 and could form a miR-31/Cdc42/phosphorylated mixed-lineage kinase 3 (p-MLK3) negative feedback loop to restrict JNK overactivation. Clinically, both miR-31 and phosphorylated JNK (p-JNK) were highly increased in liver tissues of DILI patients with different etiologies. Conclusions: miR-31 can down-regulate Cdc42 to restrict overactivation of reactive oxygen species/JNK/mitochondria necrotic death loop in hepatocytes of APAP-induced DILI, which might provide a new therapeutic target for alleviating JNK overactivation–based liver injury.